COMPARATIVE STUDY ON THE HEALTH EFFECT ASSOCIATED WITH RADON CONCENTRATION FOR BOREHOLE AND WELL WATER SAMPLES ACROSS DUTSE L.G.A, JIGAWA STATE, NIGERIA - Musa, Ibrahim Murtala; Maryam, Musbahu; Khadija, Jinjiri; Ameera, Sagir Muhammad; Samaila, Hassan; Khalid, Uba; Maimuna, Sulaiman Yakubu; Mukhtar, Dalha Imam; Ahmad, Lawan Abubakar; Muhammad, Zanna Maaji; Muhammad, Haruna Masama; Abubakar, Abdullahi Bello; et al. (FUDMA Journal of Sciences, 2026)
Groundwater contamination with naturally occurring radionuclides, poses significant environmental and health risks. This study assessed Radon-222 (^222Rn) concentrations in borehole water sources from Dutse Local Government Area (LGA), Jigawa State, Nigeria. Twenty borehole water samples were analyzed using a liquid scintillation counter. Radon concentrations ranged from 18.93 to 45.38 Bq/L, with a mean value of 28.59 Bq/L, exceeding the maximum contaminant levels (MCL) of 11.1 Bq/L (USEPA) and 10 Bq/L (WHO). The annual effective doses from ingestion for adults, children, and infants were 0.21, 0.31, and 0.34 mSv/y, respectively, all above the WHO permissible limit of 0.1 mSv/y. Excess lifetime cancer risks (ELCR) due to ingestion were 0.00073, 0.001096, and 0.001278 for adults, children, and infants, respectively, surpassing the recommended limit of 0.00029. These findings indicate that borehole water in Dutse LGA is not radiologically safe for consumption and requires treatment and routine monitoring.